Limits on Plasma Parameters in Ohmically Heated Tokamaks - Ohkawa, Tihiro (Kakuyūgō kenkyū, 1975)
The boundary conditions for heat flow in ohmically heated tokamaks are examined by using a simplified model. The analysis shows that the hot plasmas of a certain parameter, density of-1019 m-3 and confinement time of-10 msec are compatible with the boundary condition.